Pembrolizumab followed by AVD in untreated early unfavorable and advanced-stage classical Hodgkin lymphoma - Allen, Pamela B. (Blood, 2021)
Pembrolizumab, a humanized IgG4 monoclonal antibody targeting programmed death-1 protein, has demonstrated efficacy in relapsed/refractory classical Hodgkin lymphoma (cHL). To assess the complete metabolic response (CMR) rate and safety of pembrolizumab monotherapy in newly diagnosed cHL, we conducted a multicenter, single-arm, phase 2 investigator-initiated trial of sequential pembrolizumab and doxorubicin, vinblastine, and dacarbazine (AVD) chemotherapy. Patients ≥18 years of age with untreated, early, unfavorable, or advanced-stage disease were eligible for treatment. Thirty patients (early unfavorable stage, n = 12; advanced stage, n = 18) were treated with 3 cycles of pembrolizumab monotherapy followed by AVD for 4 to 6 cycles, depending on stage and bulk. Twelve had either large mediastinal masses or bulky disease (>10 cm). After pembrolizumab monotherapy, 11 patients (37%) demonstrated CMRs, and an additional 7 of 28 (25%) patients with quantifiable positron emission tomography computed tomography scans had >90% reduction in metabolic tumor volume. All patients achieved CMR after 2 cycles of AVD and maintained their responses at the end of treatment. With a median follow-up of 22.5 months (range, 14.2-30.6) there were no changes in therapy, progressions, or deaths. No patients received consolidation radiotherapy, including those with bulky disease. Therapy was well tolerated. The most common immune-related adverse events were grade 1 rash (n = 6) and grade 2 infusion reactions (n = 4). One patient had reversible grade 4 transaminitis and a second had reversible Bell’s palsy. Brief pembrolizumab monotherapy followed by AVD was both highly effective and safe in patients with newly diagnosed cHL, including those with bulky disease. This trial was registered at www.clinicaltrials.gov as #NCT03226249.